Analisis Dampak Skenario Net Zero Emission terhadap Penyediaan Energi Nasional dengan LEAP - Widhiatmaka; Joko Santosa; Nona Niode; Nurry Widya Hesty; Afri Dwijatmiko; Prima Trie Wijaya; Agus Nurrohim; Arif Darmawan; Erwin Siregar (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
The achievement of the national energy supply target based on new and renewable energy (NRE) by 2025, as stated in the National Energy Policy, is still far below expectations. This shortfall is due to the continued fossil energy dominance in all sectors. To achieve net zero emission (NZE) targets by 2060, systematic and consistent transitions from fossil fuels to NRE are essential. The fossil energy utilization (domestic and imported) is expected to decline, while the substitution with NRE will increase. This study aimed to provide a forecast analysis of national energy supply and utilization across various sectors, including household, industry, power generation, transportation, and commercial sectors, until 2060. The analysis used energy modeling simulations with business as usual (BAU) and NZE scenarios, conducted using the Low Emission Analysis Platform (LEAP) software. LEAP is an integrated, scenario-based energy model used to determine energy demand, production, and resource extraction across all economic sectors. The simulation results for the NZE scenario indicate significant reductions in fossil energy usage across all sectors compared to the BAU scenario, with an increase in NRE utilization, especially in the power generation sector. By 2060, domestic coal, natural gas, fuel oil, and liquefied petroleum gas supplies are projected to decrease by 81%, 74%, 87%, and 84%, respectively; meanwhile, the demand for petroleum remains unchanged. Overall, the supply of NRE under the NZE scenario is expected to grow by an average of 9% per year from 2019 to 2060, amounting to 2.3 times the supply in the BAU scenario.